PENERAPAN ALGORITMA RSA UNTUK PENGAMANAN FILE - Jonson Manurung; Kamson Sirait; Jonas Franky Panggabean (Jurnal Mantik Penusa, 2018)
RSA is one of the asymmetric cryptographic algorithms that uses key pairs, namely public keys and private keys. The key length can be set, where the longer the key formation bit, the harder it is to solve because of the difficulty of factoring two very large numbers. This research applies the RSA algorithm for file encryption and decryption. Based on the research that has been done, the authors can draw conclusions, namely: RSA asymmetric cryptography algorithm can be implemented for the process of encryption and decryption of data files with an extension * .txt.